La ruta del vino del Somontano de Barbastro (Huesca) como proyecto territorial de identidad cultural - Castelló Puig, Ana; Hernández Navarro, María Luz (Geographicalia, 2014)
In this paper, the product “Route of the Somontano Wine”, from the area of Barbastro (Huesca) in the region of Aragón, is presented.This is a territorial project with cultural identity which serves as a benchmark within and outside the relational context in which islocated. Wine is the glue holding all the dimensions of identity, and wine tourism is the main activity; heritage resources from the territory are considered, thanks to a good governance action as the main element.